Contrasting environmental conditions precluded lower availability of Antarctic krill affecting breeding chinstrap penguins in the Antarctic Peninsula - Salmeron, Nuria; Belle, Solenne; Cruz, Francisco Santa; Alegria, Nicolas; Finger, Julia Victoria Grohmann; Cora, Denyelle Hennayra; Petry, Maria Virginia; Hernandez, Cristina; Cardenas, Cesar A.; Kruger, Lucas (My University, 2023)
Dramatic decreases of chinstrap penguin populations across the Antarctic Peninsula (AP) are thought to be influenced by climate-driven changes affecting its main prey, the Antarctic krill, however, empirical evidence supporting such hypotheses are scarce. By coupling data on breeding chinstrap penguins, environmental remote sensing and estimates of krill acoustic density, we were able to demonstrate that penguins substantially increased their foraging effort in a year of low krill availability, with consequent reduction in breeding success. A winter of low sea ice cover followed by a summer/spring with stronger wind and lower marine productivity explained the lower and deeper krill availability. Our results highlight the importance of environmental variability on penguin populations, as variability is expected to increase under climate change, affecting foraging behaviour responses.
Keywords: Antarctic krill; Peninsula; Pygoscelis